On Tailoring Co-Precipitation Synthesis to Maximize Production Yield of Nanocrystalline Wurtzite ZnS - Radenka Krsmanović Whiffen; Amelia Montone; Loris Pietrelli; Luciano Pilloni (Nanomaterials, 2021)
Pyroelectric materials can harvest energy from naturally occurring ambient temperature changes, as well as from artificial temperature changes, notably from industrial activity. Wurtzite- based materials have the advantage of being cheap, non-toxic, and offering excellent opto-electrical properties. Due to their non-centrosymmetric nature, all wurtzite crystals have both piezoelectric and pyroelectric properties. Nanocrystalline wurtzite ZnS, being a room temperature stable material, by contrast to its bulk counterpart, is interesting due to its still not well-explored potential in piezoelectric and pyroelectric energy harvesting. An easy synthesis method—a co-precipitation technique—was selected and successfully tailored for nanocrystalline wurtzite ZnS production. ZnS nanopowder with nanoparticles of 3 to 5 nm in size was synthesized in ethyl glycol under medium temperature conditions using ZnCl2 and thiourea as the sources of Zn and S, respectively. The purified and dried ZnS nanopowder was characterized by conventional methods (XRD, SEM, TEM, TG and FTIR). Finally, a constructed in-house pilot plant that is able to produce substantial amounts of wurtzite ZnS nanopowder in an environmentally friendly and cost-effective way is introduced and described.